KAJIAN PENANGGULANGAN AIR ASAM TAMBANG PADA SALAH SATU PERUSAHAAN PEMEGANG IJIN USAHA PERTAMBANGAN DI DESA LEMO, KABUPATEN BARITO UTARA, KALIMANTAN TENGAH - Susan Nadya Irawan; Idiannor Mahyudin; Fakhrur Razie; Susilawati Susilawati (EnviroScienteae, 2016)
This study aims to know the factors that cause the formation of Acid Mine Water, to analyze the methods of prevention of acid mine drainage has been running effectively, to analyze how to prevent the formation of acid mine water at the research area. This research was conducted atLemovillage,North Barito Regency. These results indicate the analysis of water quality in the company with an indication acidic low pH values and high metal values. It is supported by soil pH test results showed low pH, especially on the layer in direct contact or close to coal. Sources of acid mine drainage at the company are from the oxidation of water and oxygen on the wall of rock at pit, water from the dumping area, water flowing from the temporary stockpile into the settling pond 2. From these, we can conclude the results. Recommendations prevention of acid mine drainage can be done by moving the location of the temporary stockpile in accordance with, more effective functioning of sump, controlling the movement of acidic water that has formed, accommodate and neutralize the acidic water that has formed, forming a layer of dry cover, separating the flow of water is not acidic and acidic